2018
DOI: 10.1111/jonm.12509
|View full text |Cite
|
Sign up to set email alerts
|

When nurse emotional intelligence matters: How transformational leadership influences intent to stay

Abstract: Nurse leaders should develop training programmes to improve nursing manager transformational leadership and staff nurse emotional intelligence in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 45 publications
(47 reference statements)
3
46
0
3
Order By: Relevance
“…The leadership role of nursing managers is of great significance to the cohesion of the team, and the leadership style is the main embodiment of leadership. Wang et al 38 showed that the transformational leadership style was positively correlated with nurses' intent to stay. Japanese researcher Kodama 39 further analyzed the components of the transformational leadership style and found that the intellectual stimulation factor in the transformational leadership style was an important factor to enhance nurses' emotional commitment to the organization and their willingness to retain their posts.…”
Section: Leadership Factormentioning
confidence: 99%
“…The leadership role of nursing managers is of great significance to the cohesion of the team, and the leadership style is the main embodiment of leadership. Wang et al 38 showed that the transformational leadership style was positively correlated with nurses' intent to stay. Japanese researcher Kodama 39 further analyzed the components of the transformational leadership style and found that the intellectual stimulation factor in the transformational leadership style was an important factor to enhance nurses' emotional commitment to the organization and their willingness to retain their posts.…”
Section: Leadership Factormentioning
confidence: 99%
“…Previous studies on EI include cross-sectional studies of student subjects (Chan and Hamamura, 2016; Orak et al, 2016; Stiglic et al, 2018), investigations of the relationship with burnout (Taylor et al, 2015; Chao et al, 2016), and investigations of the relationship with nursing management (Lucas et al, 2008; Spano-Szekely et al, 2016). Actual EI in nursing outside Japan has been demonstrated in countries including Netherlands, South Korea, and China, and while the characteristics differ depending on the assessment scale used and the country surveyed, the need for continuous education and follow-up has been suggested (Van Dusseldorp et al, 2011; Wang et al, 2014, 2018; Sims, 2017). However, EI in Japanese nurses has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership and values, including transformational leadership, structural empowerment, nurse participation in hospital affairs and organisational values, were examined in 11 studies (Chen, Li, Li, Lyu, & Zhang, 2018; Guo et al., 2016; Liu, You, Zheng, Ross, & Liu, 2016; Liu, Zheng, Liu, & You, 2019; Liu et al., 2018; Liu, While, Li, & Ye, 2015; Shao et al., 2018; Wan, Li, Zhou, & Shang, 2018; Wang, Tao, Bowers, Brown, & Zhang, 2018; Yang, Liu, Chen, & Pan, 2014; Zhang et al., 2014).…”
Section: Resultsmentioning
confidence: 99%